PRINCIPLES OF EPISTEMOLOGICAL FOUNDATIONS OF BUSINESS PROCESS MANAGEMENT IN PROVIDING AN ENTERPRISE ECONOMIC SECURITY (Development Service Industry Management, 2025)
The principles of content and the principles of using epistemological foundations for managing business processes in ensuring the economic security of an enterprise are proposed. The principles of content should be applied during the construction of the relevant foundations up to the moment of their use, while the principles of using such foundations should be applied after the foundations are constructed and during their use.The components of the principles of content of the epistemological foundations for managing business processes in ensuring the economic security of an enterprise include ontological certainty, scientific justification, proven validity, excessive completeness, objectivity, systematic approach, logical coherence, conceptual pluralism, structuring, completeness, internal coherence, and interdisciplinarity. The content of each of these principles is revealed and described.The principles for using the epistemological foundations for managing business processes in ensuring the economic security of an enterprise include multicombinability, universality, the anthropic factor, the subjectivity of managerial influence, methodological variability, epistemological additivity, practical completeness of interpretation, unambiguous interpretation, instrumental adequacy, empirical verifiability, the possibility of practical operationalization, and practical value. The content of each of these principles is provided and described.The negative consequences of non-compliance with each of the highlighted principles in the groups of principles of content and use of the epistemological foundations for managing business processes in ensuring the economic security of an enterprise are demonstrated.
Keywords: economic security of an enterprise; business process; management; principle; content; use; consequences of non-compliance